One Pillar Crumbling, the Others too Short: Old-Age Provision in Germany - Martin Werding (Center for Economic Studies and ifo Institute (CESifo), 2016)
Public pay-as-you-go pensions still form the dominant pillar of old-age provision in Germany. This is in marked contrast to the situation in Anglo-Saxon countries. It has advantages if labour markets are strong, e.g., following a quick recovery from the Great Recession. It has disadvantages, as Germany will be ageing very rapidly in the near future. Following a series of reforms, benefit levels will decline, while contribution rates still go up, and additional cover from private or occupational pension schemes is urgently needed. Thus far, steps in this direction have been half-hearted, and the financial crisis impedes a further shift. Nevertheless, despite the differing traditions, important aspects in current debates now converge to those discussed in the UK or the US.
Keywords: E27; G28; H55; J11; J26; 330; old-age provision; public pensions; occupational pensions; pre-cautionary saving; demographic ageing; pension reform; simulations